Визначення енергоефективності акустичних пристроїв в оптичній транспортній мережі за допомогою 3D-аналізу коефіцієнта електромеханічного зв’язку - Кайдан, М. В. (Видавництво Львівської політехніки, 2016)
Досліджено коефіцієнт електромеханічного зв’язку. Описано модель дослідження 3D-аналізу просторової анізотропії акустичних параметрів. Подано алгоритм побудови вказівної поверхні коефіцієнта електромеханічного зв’язку на основі рівнянь Гріна–Крістофеля. Вперше побудовано вказівні поверхні коефіцієнта електромеханічного зв’язку. Визначено максимальні значення для побудованих поверхонь. Для поперечної поляризації визначено напрямки, які дають змогу на 3 % енергоефективніше використовувати п’єзоперетворювачі на основі кристалів LiNbO3. Показана необхідність подальшого проведення досліджень просторового розподілу коефіцієнта електромеханічного зв’язку. In this paper we investigate electromechanical coupling coefficient. We show the investigation importance of spatial distribution coefficient of electromechanical coupling. This parameter characterizes the energy efficiency of piezoelectric transducer that in turn affects the acousto-optic devices in optical transport networks. We present basic definitions and types of electromechanical coupling coefficient. We also show the formula for determining the coefficient of electromechanical coupling that facilitates study of the spatial distribution of this coefficient. We present a research model of spatial anisotropy for acoustic parameters and prospose an algorithm for constructing the indicative surface of electromechanical coupling coefficients for a particular direction of the radius vector. The radius vector coincides with the direction of acoustic waves propagtion by using the equation Green-Christoffel. We show the adequacy of the results by analyzing previous studies conducted on the plane X2X3 in LiNbO3 crystals. The indicative surface coefficients of electromechanical coupling have been constructed for the first time. This surfaces have been analyzed and maximum values have been defined. The indicative surfaces of electromechanical coupling coefficients do not exhibit a totally rotational symmetry with the axis of infinity order, what appears to be also consistent with the German’s theorem. According to the principle of Curie-Neumann, the indicative surface is invariant here with respect to the symmetry operations of the point group 3m that describe the symmetry of the crystal structure of LiNbO3 crystals. The directions of efficient use of LiNbO3 crystal for acoustic device were determined. For transverse polarization directions of efficient 3 % utilization of piezoelectric transducer crystals LiNbO3 were determined. For longitudinal polarization the directions that could improve energy efficiency of acoustic devices were not found. We stress that further studies of the spatial distribution coefficient of electromechanical coupling to other piezoelectric materials should be conducted. We have concluded that the values of the sample orientation are different from the direction of the main planes of the sample and symmetry planes.
Determination of energy efficiency acoustic devices in the optical transport network using 3D-analysis of electromechanical coupling
Keywords: коефіцієнт електромеханічного зв’язку; вказівна поверхня; поляризація акустичної хвилі; енергоефективність; electromechanical coupling; the indicative surface; polarization of acoustic wave; energy efficiency